Utilization of Social Media and Online Platforms in Improving Customer Engagement of Fashion SMEs in Bali - Arjang, Arjang; Utami, Eva Yuniarti; Redjeki, Finny (Westscience Press, 2024)
This research investigates the intricate dynamics of social media utilization and online platform presence in shaping customer engagement for small and medium-sized fashion enterprises (SMEs) in Bali. A sample of 120 fashion SMEs participated in a cross-sectional survey, providing insights into their digital strategies and customer interactions. The study employs Structural Equation Modeling with Partial Least Squares (SEM-PLS) to analyze the relationships between social media utilization, online platform presence, and customer engagement. Descriptive statistics, reliability, and validity analyses are conducted to ensure the robustness of the measurement model. The findings reveal a positive and significant impact of social media utilization on online platform presence and, subsequently, customer engagement. The mediating role of online platforms in enhancing customer interactions is highlighted. Practical implications and recommendations are provided for fashion SMEs seeking to optimize their digital strategies and foster meaningful customer engagements in the vibrant cultural context of Bali.